Legal Consequences of Notarial Deeds Regarding Negligence in Typing Errors in Notarial Deeds - Mu’alimah, Nurul; Alia Maerani, Ira (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
Notaries must be guided by divine values, human values, justice values, ethical values (adab), unity values, people's values, deliberative values, national values, and other values that are upheld by the Indonesian people. The public places great trust in Notaries. However, Notaries are ordinary people who can make mistakes. One of the errors that can occur is a typo in the Notary's deed. Mistakes and negligence made by the Notary when carrying out his duties can have an impact on the deed he makes. The purpose of this research is to find out: 1) The legal consequences of a deed that has typographical errors in the deed made by the Notary. 2) Efforts taken if a typo occurs. 3) The Notary's responsibility in making the deed if a typographical error occurs. The approach method in this research is sociological juridical. The results of the research concluded: 1) The legal consequences if a Notary makes a typing error in his or her deed due to negligence or lack of care alone can result in civil and administrative sanctions. 2) Typical errors in notarial deeds can be substantive or non-substantive. A non-substantive typographical error means that the error does not cause a significant difference in meaning in the substance of the deed or even if there is a difference in the meaning of words, but in the context of the sentence it cannot be interpreted differently from what is actually intended, including errors in spelling. 3) Article 51 UUJN gives the Notary the authority to correct written errors or typographical errors contained in the Minutes of the signed deed. Keywords: Deed; Error; Notarial; Typing.